The effect of high swirl on reducing emissions from liquid fuel burner system - Mohamad Shaiful Ashrul, Ishak; Mohammad Nazri, Mohd. Jaafar (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 15th June 2006 at DKG 4 & DKG 5, Kubang Gajah, Arau, Perlis.